Clinical outcomes of AML patients treated with Azacitidine in Portugal: A retrospective multicenter study. (2017) - Almeida, António; Ferreira, Ana Rita; Costa, Maria João; Silva, Sofia; Alnajjar, Khalil; Bogalho, Isabel; Pierdomenico, Francesca; Esteves, Susana; Alpoim, Mafalda; Braz, Gil; Cortesão, Emilia; Pinto, Ricardo
Abstract: Retrospective data was collected from 77 elderly acute myeloid leukemia (AML) patients treated with Azacitidine (AZA) and 50 elderly AML patients treated with intensive chemotherapy (IC) from 4 Portuguese Hospitals. Median OS was 10.6 months in those receiving AZA as 1st line. Response (overall response rate 44%) had a significant impact on overall survival (p=<0.0001). Median OS of the comparator IC cohort was significantly inferior to that observed in the cohort treated with AZA in first line (p=0.0104). These results support the efficacy of AZA in AML in the elderly in any line of treatment.